2002
DOI: 10.1128/iai.70.3.1225-1229.2002
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Diversity of Escherichia coli Colonizing Stools and Urinary Tracts of Young Girls

Abstract: Intestinal carriage of Escherichia coli in prepubertal girls without a history of urinary tract infection was examined by collecting weekly stools and periurethral and urine samples over 3 to 4 weeks of study. Dominant and minor clones were defined by grouping 28 E. coli isolates into clonal types. Multiple enteric clones of E. coli, which changed week to week, were found in the 13 girls during the study (median, 3 clones/girl; range, 1 to 16 clones/girl). Dominance of an enteric clone did not predict persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
76
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 17 publications
7
76
0
Order By: Relevance
“…This study isolates were dominated by group A (66.3%), as it was shown in previous studies [28,29] that the E. coli clonal community of a person is numerically dominated by one strain, or at most a few strains. Other researchers [13,27,30] found much more prevalence of phylogroup B2 among fecal isolates in comparison with this study results.…”
Section: Discussionsupporting
confidence: 72%
“…This study isolates were dominated by group A (66.3%), as it was shown in previous studies [28,29] that the E. coli clonal community of a person is numerically dominated by one strain, or at most a few strains. Other researchers [13,27,30] found much more prevalence of phylogroup B2 among fecal isolates in comparison with this study results.…”
Section: Discussionsupporting
confidence: 72%
“…Several studies have shown the existence of a temporal variability in the incidence of commensal E. coli populations at the year level (21), month level (23), or week level (25), mostly in humans but also in cattle and horses (29). This study followed on a daily basis and over a 25-day period the commensal E. coli populations of healthy adult cows in an extensive small-scale farming system with a focus on subpopulations of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most of the few studies that have aimed to obtain an understanding of the temporal dynamics of E. coli populations show that a high degree of clonal diversity exists over years (21), months (22,23), or weeks (24,25). Combined with the already known intermittent nature of the shedding of STEC in cattle (9,26), these studies highlight the fact that a precise description of the dynamic pattern at the clonal level requires shorter sampling intervals.…”
mentioning
confidence: 99%
“…The impact of different sampling strategies on the characterization of E. coli colonization is unclear. Most studies that have investigated this issue have focused on only specific types of E. coli (e.g., diarrheagenic E. coli or E. coli O157) (4,8,11), studied nonhuman fecal samples (1,2,8,11), and/or included a small sample size of subjects (Ïœ20) (1,2,9,11). Indeed, past studies of E. coli have often selected a relatively small number (i.e., Յ10) of colonies on which to base their investigation of strain diversity (6,8).…”
mentioning
confidence: 99%